An upconversion nanosensor with phenolic-like functionality for accurate identification of chlorpyrifos in grapes. (1st August 2023) - Wu, Meng; Yi, Jiaqi; Yin, Chenhui; Sun, Qijun; Gao, Lei; Niu, Na; Chen, Ligang
Highlights: Developed a UCNPs-COOH/Rdp fluorescent probe for chlorpyrifos recognition. The fluorescent probe has high sensitivity and stability. NIR excitation light source can avoid some non-target fluorescence interference. The chlorpyrifos sensing probe has been successfully applied to grape samples. Abstract: The inappropriate use of the organophosphorus pesticide chlorpyrifos (CPF) in agricultural production could be harmful to the environment and non-target organisms. Here, we prepared a nano-fluorescent probe with phenolic function based on covalently coupled rhodamine derivatives (RDP) of upconverted nano-particles (UCNPs) for trace detection of chlorpyrifos. Due to the fluorescence resonance energy transfer (FRET) effect in the system, the fluorescence of UCNPs is quenched by RDP. The phenolic-functional RDP is converted to the spironolactone form when it captures chlorpyrifos. This structural shift prevents the FRET effect in the system and allows the fluorescence of UCNPs to be restored. In addition, the 980 nm excitement conditions of UCNPs will also avoid interference from non-target fluorescent backgrounds. This work has obvious advantages in terms of selectivity and sensitivity, which can be widely applied to the rapid analysis of chlorpyrifos residues in food samples.